A Study of the level of Self-Esteem among B.Sc Nursing Students: Examining the Impact of Self-Esteem on B.Sc Nursing Students (Journal of Advances and Scholarly Researches in Allied Education, 2020)
This study aims to examine the level of self-esteem among B.Sc Nursing students. Self-esteemis a crucial psychological construct that influences individuals' overall well-being and performance.Understanding the self-esteem levels of nursing students is essential, as it may have implications for theiracademic success, personal development, and future nursing practice. The study will employ aquantitative research design and utilize a standardized self-esteem measurement scale. Data will becollected from a sample of B.Sc Nursing students using a structured questionnaire. The findings of thisstudy will provide valuable insights into the self-esteem levels of B.Sc Nursing students, highlightingareas that may require attention and support within nursing education.